G-Protein β Subunit of Cochliobolus heterostrophus Involved in Virulence, Asexual and Sexual Reproductive Ability, and Morphogenesis - Ganem, Sherif (American Society for Microbiology, 2004)
Previous work established that mutations in mitogen-activated protein (MAP) kinase (CHK1) and heterotrimeric G-protein α (Gα) subunit (CGA1) genes affect the development of several stages of the life cycle of the maize pathogen Cochliobolus heterostrophus. The effects of mutating a third signal transduction pathway gene, CGB1, encoding the Gβ subunit, are reported here. CGB1 is the sole Gβ subunit-encoding gene in the genome of this organism. cgb1 mutants are nearly wild type in vegetative growth rate; however, Cgb1 is required for appressorium formation, female fertility, conidiation, regulation of hyphal pigmentation, and wild-type virulence on maize. Young hyphae of cgb1 mutants grow in a straight path, in contrast to those of the wild type, which grow in a wavy pattern. Some of the phenotypes conferred by mutations in CGA1 are found in cgb1 mutants, suggesting that Cgb1 functions in a heterotrimeric G protein; however, there are also differences. In contrast to the deletion of CGA1, the loss of CGB1 is not lethal for ascospores, evidence that there is a Gβ subunit-independent signaling role for Cga1 in mating. Furthermore, not all of the phenotypes conferred by mutations in the MAP kinase CHK1 gene are found in cgb1 mutants, implying that the Gβ heterodimer is not the only conduit for signals to the MAP kinase CHK1 module. The additional phenotypes of cgb1 mutants, including severe loss of virulence on maize and of the ability to produce conidia, are consistent with CGB1 being unique in the genome. Fluorescent DNA staining showed that there is often nuclear degradation in mature hyphae of cgb1 mutants, while comparable wild-type cells have intact nuclei. These data may be genetic evidence for a novel cell death-related function of the Gβ subunit in filamentous fungi.